Determination of Financial Management in Indonesia - Ni Nyoman sawitri (Greenation International Journal of Economics and Accounting, 2024)
The article on determining financial management in Indonesia is a scientific literature review article within the scope of financial management science. This article aims to create a hypothesis regarding the relationship between factors, which can then be used for further research in the field of financial management. Descriptive qualitative research methodology was used in this research. The data used in this research comes from previous research which is still relevant to this research. Data was obtained from reputable academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and the journal Sprott. The results of this research are as follows: 1) The capital market plays a role in Financial Management in Indonesia; 2) Monetary policy plays a role in Financial Management in Indonesia; 3) Fiscal policy plays a role in Financial Management in Indonesia; and 4) Economic growth plays a role in Financial Management in Indonesia.